Abnormal Orientation of the Superior Mesenteric Vessels Detected in Asymptomatic Infants: What Is Its Destiny? - Son, Joonhyuk; Lee, Sanghoon; Kim, Wontae; Jung, Soo-Min; Jeon, Tae Yeon; Yoo, So-Young; Kim, Ji Hye; Seo, Jeong-Meen (Frontiers in Pediatrics, 2021)
Background: Ultrasonography (USG) has been described as an alternative diagnostic tool for malrotation that evaluates the orientation of the superior mesenteric vessels. However, literature concerning the management of patients who do not have abdominal symptoms is limited. We aimed to review the clinical course of infants showing abnormal orientation of the superior mesenteric vessels on USG who were asymptomatic at the time of diagnosis. Methods: Seventy asymptomatic infants with abnormal orientation of the superior mesenteric vessels in a single center between 2014 and 2018 were retrospectively analyzed. Results: Of the 70 patients, 21 underwent upper gastrointestinal series (UGIS) and 11 underwent abdominal surgery for other surgical conditions. Among the 32 (45.7%) patients who underwent UGIS or abdominal surgery, 11 were proven to have malrotation. Of the 38 (54.3%) patients who did not undergo UGIS or abdominal surgery, six patients were too unstable to undergo UGIS, five died due to cardiac complications, and the remaining patient developed midgut volvulus and died three days after emergency surgery. The remaining 32 patients who did not undergo UGIS or abdominal surgery were discharged without additional tests, and all were asymptomatic until their last follow-up. In the multivariate analysis, history of heart surgery and the presence of more than three anomalies were significantly associated with malrotation. Conclusion: A significant number of malrotation were diagnosed in asymptomatic infants with abnormal orientation of the superior mesenteric vessels on USG. Infants with major cardiac or multiple anomalies need special attention and should undergo UGIS in a promptly manner to confirm malrotation.